Credit Crises and the Shortcomings of Traditional Policy Responses - White, William R.. (OECD Economics Department Working Papers, 2012)
Economic downturns which have their roots in preceding credit excesses and debt overhang have tended historically to be long lasting, whether the financial sector remained healthy or not. There are no good reasons to believe the current global crisis will be any different. Moreover, it is argued in this paper that the policy responses to the crisis to date, both macroeconomic and structural, will not succeed in restoring sustainable growth. Monetary and fiscal stimulus might raise aggregate demand in the short run, but they contribute to higher debt levels which are already working increasingly in the opposite direction. Structural policies intended to maintain pre crisis production patterns, both in the financial and industrial sectors, ignore the unsustainability of those structures in the first place. Alternative policies are needed to meet the G 20's goal of "strong, sustainable and balanced growth". They include more international cooperation between creditor and debtor countries (on both exchange rates and production structures), more recourse to explicit debt restructuring (for both households and sovereigns), and structural polices to raise potential growth and make debts more sustainable. Unfortunately, there remain formidable practical and political obstacles to pursuing such policies. Future debt crises of the current magnitude could be avoided by using monetary, macro prudential and fiscal policies more symmetrically over the business cycle. Relative to past behaviour, this would imply more vigorous resistance to credit financed upswings, and a greater willingness to accept the cleansing effect of minor downswings. Policies to ensure financial stability are important but secondary